The role of chromatin modifications in somatic embryogenesis in plants - De-la-Peña, Clelia; Nic-Can, Geovanny I.; Galaz-Ávalos, Rosa M.; Avilez-Montalvo, Randy; Loyola-Vargas, Víctor M. (Frontiers in Plant Science, 2015)
Somatic embryogenesis (SE) is a powerful tool for plant genetic improvement, when used in combination with agricultural traditional techniques, and it is being used to understand the different processes that occur during the development of plant embryogenesis. SE onset depends on a complex network of interactions among plant growth regulators, mainly auxins and cytokinins, during the proembryogenic early stages, and ethylene, gibberellic and abscisic acids later in the development of the somatic embryos. These growth regulators control spatial and temporal regulation of multiple genes in order to initiate the change in the genetic program of the somatic cells, as well as the transition among embryo developmental stages. In recent years, epigenetic mechanisms have emerged as critical factors during SE. Some early reports indicate that auxins modify the levels of DNA methylation in embryogenic cells. The changes in DNA methylation patterns are associated with the regulation of several genes involved in SE, such as WUS, BBM1, LEC, and several others. In this review, we highlight the more recent discoveries in the role of epigenetic regulation of SE. In addition, we include a survey of novel approaches to the study of SE, and new opportunities to focus SE studies.